Analyzing Micro, Small, and Medium Enterprises' Taxpayer Compliance Through Tax Socialization, Tax Penalties, and e-Form Implementation - Devi Devi; Janiman Janiman (Jurnal Akuntansi, 2026)
Purpose – This research is intended to analyze the influence of tax socialization, tax penalties, and the application of the e-form system on the level of compliance among Micro, Small, and Medium Enterprises (MSMEs) taxpayers. Design/Methodology/Approach – The study employs primary data obtained through questionnaires administered to MSME taxpayers registered at KPP Pratama Cirebon Satu. A purposive sampling technique was applied in selecting the sample, resulting in a total of 393 respondents. The collected data were processed and examined using the Partial Least Squares (PLS) method supported by the SmartPLS software. Results –  The findings reveal that tax socialization, tax sanctions, and the use of the e-form system positively influence MSME taxpayer compliance. These results indicate that enhancing the effectiveness of tax socialization programs, implementing stricter enforcement of tax penalties, and facilitating easier reporting through the e-form system can significantly improve the compliance behavior of MSME taxpayers. Research limitations/Implications – This study is limited to MSME taxpayers registered at KPP Pratama Cirebon Satu and only examines three independent variables affecting taxpayer compliance. The results of this study provide implications for tax authorities in designing more effective tax education programs, strengthening law enforcement through tax sanctions, and improving digital tax reporting systems to enhance MSME taxpayer compliance. Keywords: e-Form, MSME Taxpayer Compliance, Tax Sanctions, Tax Socialization